Analisis Sistem Informasi Akuntansi dalam Penawaran Shopee Flash Sale dan Shopee Paylater Terhadap Perilaku Impulsive Buying pada Generasi Z - Aswani Mentari Pratista; Diana Airawaty (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
The rapid growth of e-commerce in Indonesia, led by Shopee, has intensified impulsive buying among Generation Z through features like Flash Sale and PayLater, supported by Accounting Information Systems (AIS). This study aims to analyze AIS implementation in these offers and their partial/simultaneous impact on impulsive buying behavior. Employing a quantitative approach, purposive sampling targeted 100 active Shopee users (Gen Z, born 1997-2008) in Central Java and Yogyakarta. Data from Likert-scale questionnaires were analyzed via SPSS multiple linear regression, including validity/reliability tests, classical assumptions, t-test, F-test, and R². Results reveal Flash Sale (β=0.927, t=3.601, p=0.001) and PayLater (β=0.304, t=2.362, p=0.020) significantly influence impulsive buying both partially and simultaneously (F p=0.000), with R²=36.5%. In conclusion, while AIS enhances real-time efficiency, other factors explain 63.5% variance; Shopee should promote ethical marketing and financial literacy.